The influence of academic ability and learning styles on learning outcomes in differentiated instruction - Wahyuni, Arie; Abidin, Zaenal; Ismail, Agus Yadi; Aminudin, Sukron (STKIP Persada Khatulistiwa Sintang, 2025)
Applying students' learning styles and academic abilities often poses a challenge in the differentiated learning process. This study investigates the influence of learning styles and academic ability on student learning outcomes in the differentiated learning process of plant and animal reproduction material. With the quasi-experimental method and pretest-posttest control design. The subjects of the research were ninth-grade students at UPTD SMPN 1 Losarang. Learning style data, the academic groups of students from the pre-test results in the high ability group predominantly having an auditory learning style, the middle ability group predominantly having a kinesthetic learning style, and the low ability group predominantly having a visual learning style. There is no influence of learning style on learning outcomes of 2.9%. There is a positive and significant influence of academic ability on learning outcomes of 48%. There is a positive and significant influence of learning style and academic ability on learning outcomes of 49.8%. The T-test for the experimental and control classes produced output Pair 1 with a sig value of 0.000 < 0.05, meaning there is an influence of learning styles and academic ability on student learning outcomes in differentiated learning before and after treatment.